Peran Usaha Walet Dalam Meningkatkan Pendapatan Masyarakat Desa Sumber Agung Kab. Muaro Jambi - Ahmad Taufik Murtadho; Hansen Rusliani; Sri Rahma (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Swiftlet's nest is one of the most famous foods in the world. Swiftlet's nest is believed to have very good benefits for the health of the human body. This swallow nest besides having a high price, can also be beneficial for the world of health. In order to get high-value swallow nests, it is necessary to know the types of swallows that can produce good quality nests. This study uses the theory of income in the book development economics by Sukirno Sadono. The research aims to determine the role of the swallow business in increasing the income of the Sumber Agung community. This research includes field research, with the method of observation, interviews and documentation, while the data analysis used is qualitative data analysis. The results of the study show that the swallow's nest breeding business in Sumber Agung Village is a side business where the average community in Sumber Agung Village has a livelihood as oil palm farmers. The swallow's nest breeding entrepreneurs aim to improve the family's economy by looking at the high selling price of swallow's nests and export value. The risks faced can also be minimized so that there are no substantial losses.